2016
DOI: 10.1101/077784
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resting high frequency heart rate variability is not associated with the recognition of emotional facial expressions in healthy human adults

Abstract: This study explores whether the myelinated vagal connection between the heart and the brain is involved in emotion recognition. The Polyvagal theory postulates that the activity of the myelinated vagus nerve underlies socio-emotional skills. It has been proposed that the perception of emotions could be one of this skills dependent on heart-brain interactions. However, this assumption was differently supported by diverging results suggesting that it could be related to confounded factors. In the current study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…Next, participants had to equip themselves with electrodes following prior instructions and a schema stuck on a mirror. Once equipped, participants sat at a desk in front of a television, with knees at a 90° angle and arms resting on the desk, and they had to watch a 5-minute soundless video clip to reach a quiet state (see Beffara et al, 2016). Then, participants listened to a 6minute neutral audio extract presenting the first part of the giraffe's Wikipedia page (i.e., size, height, alimentation, Bertels et al, 2014) and we recorded baseline-HRV at this moment.…”
Section: Methodsmentioning
confidence: 99%
“…Next, participants had to equip themselves with electrodes following prior instructions and a schema stuck on a mirror. Once equipped, participants sat at a desk in front of a television, with knees at a 90° angle and arms resting on the desk, and they had to watch a 5-minute soundless video clip to reach a quiet state (see Beffara et al, 2016). Then, participants listened to a 6minute neutral audio extract presenting the first part of the giraffe's Wikipedia page (i.e., size, height, alimentation, Bertels et al, 2014) and we recorded baseline-HRV at this moment.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that the RMET captures ToM deficits shown by people with ASD more than other tests do (Peterson and Slaughter, 2009) because it requires not only the identification of primary emotions from facial expression but also the recognition of mental states from a specific portion of the face. In fact, the understanding of inner states is more complex than the recognition of primary emotions, which has been more deeply investigated in relation to the vagal modulation of the heart (Bal et al, 2010;Park et al, 2012;Quintana et al, 2012;Beffara et al, 2016b;Lischke et al, 2017).…”
Section: Summary Of Main Findingsmentioning
confidence: 99%